Dating in the dark: A qualitative examination of dating experiences in Dark Tetrad personalities. (June 2023) - Mayshak, Richelle; Howard, Dominika; Benstead, Michelle; Klas, Anna; Skvarc, David; Harries, Travis; Patafio, Brittany; Sleep, Abby; King, Ross; Hyder, Shannon
Abstract: Dark Tetrad (D4) traits have been shown to influence both perpetration and victimisation of dating related anti-social behaviours. To inform prevention and intervention measures against these behaviours, it is important to understand how persons with elevated D4 traits search for partners and what aspects of dating they appraise as positive versus negative. This study aims to qualitatively explore the role of personality in dating experiences; specifically, preference for dating platform and perceived dating outcomes in those with elevated D4 traits. In total, 480 adults from Australia, (288 women, 186 men, and 6 non-binary) aged 18– 70 years ( M = 29.51, SD = 12.82), took part in an online qualitative and quantitative survey. Participants with elevated traits of psychopathy, narcissism and sadism showed a greater preference for meeting people offline. Applying template analysis, we generated three themes for positive experiences: finding a new partner, connecting with others, and material and personal benefits. For negative experiences, we identified four themes: not being able to find a partner, misrepresentation, online and in-person victimisation, and difficulties with navigating close relationships. Whilst persons with elevated D4 traits value connecting with others, they dislike deceptive dating practices and often perceive themselves to be victimised in online and offline settings. Future studies should investigate whether dating experiences differ across individuals who score within elevated versus lower range on D4 traits. Highlights: Elevated scores on some of the D4 traits are linked to preferences for offline dating. Men with elevated D4 traits reported sexual experiences as positive aspects of dating. Social approval/emotional validation was appraised as a positive dating outcome . Women with elevated D4 traits reported instances of online and offline victimisation. Elevated D4 traits linked to rejection sensitivity and broader relationship issues.